HOUSEKEEPING PRACTICES IN BSHM BESTLINK COLLEGE OF THE PHILIPPINES: SCHOOL-BASED TRAINING INTO ON-THE-JOB EXPERIENCE (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The study examines the impact of combining school-based training and on-the-job training (OJT) on the development of housekeeping skills among Bachelor of Science in Hospitality Management (BSHM) students at Bestlink College of the Philippines. It focuses on how classroom instruction, including theoretical lessons and simulated housekeeping activities, prepares students for practical application during their internship at Astoria Plaza. The research aims to determine whether integrating academic learning with real-world experience effectively enhances students’ technical proficiency, work readiness, and overall performance in the hospitality industry. This study utilized a quantitative research approach with a descriptive survey design to evaluate the effectiveness of integrated training on the housekeeping skills of BSHM students. A purposive sampling method was employed to select 100 fourth-year students currently participating in their on-the-job training (OJT). Data collection was conducted through a validated questionnaire that measured multiple aspects of both school-based instruction and industry-based training, including butler and valet services, bed-making, laundry and linen handling simulations, job preparedness, workplace performance, and professional conduct. The gathered data were subjected to statistical analysis using percentage distributions and weighted means, along with inferential tests to explore potential relationships among the identified variables. The study revealed a strong level of agreement among respondents regarding the effectiveness of both school-based training and on-the-job training (OJT) in developing their housekeeping competencies. Students reported a high degree of satisfaction with simulation-based learning, particularly in key areas such as butler services, bed making, and laundry and linen management. These structured simulations, combined with real-world exposure during their internship at Astoria Plaza, significantly contributed to their job preparedness, skill mastery, and professional growth. However, despite these positive outcomes, the respondents also identified several critical limitations within the training program. Among the most cited challenges were outdated equipment, insufficient and overcrowded training facilities, and limited time allocated for practical sessions—all of which were perceived as barriers to optimizing hands-on learning experiences and achieving higher levels of competency. The findings of this study emphasize the value of integrating school-based instruction with on-the-job training (OJT) in hospitality education. This dual approach not only equips students with practical competencies but also enhances their confidence, motivation, and sense of professionalism. The seamless connection between academic simulations and actual industry experience ensures that students are better prepared to meet workplace demands. Nonetheless, the effectiveness of these training programs could be significantly improved by addressing persistent challenges, including limited resources, outdated equipment, and insufficient time for hands-on learning.
Keywords: hospitality education; housekeeping skills; school-based training; on-the-job training (ojt); practical simulation; student internship; professional development; resource limitations; bachelor of science in hospitality management (bshm); bestlink college